Arqueas Halófilas productoras de Betacaroteno aisladas de las salinas solares de Huacho-Lima - Esquerre, Cynthia G. (2003)
Throughout the world, interest toward the search of natural sources of betacarotene has beenincreased due to its wide use as a colorant and antioxidant agent in pharmaceutical, cosmetic and food industries. In order to isolate Archaea halophilics betacarotene producers, salt samples from solar saltems located in Huacho were taken and cultured in sea water agar (SWA) supplemented with 20% NaCl and 0.5% yeast extract.. From the 25 microorganisms isolated, 12 which presented difierent reddish cellular pigmentation were chosen. Selected isolates were analyzed to determine their cellular growth and ability to produce betacarotene, being the isolate W2 which obtained the highest cellular pigmentation index. Besides, optimal concentration of NaCl and yeast extract to increase the production of betacarotene was determined. Isolate W2 was identified as Haloferax gibbonsii of the Archaea domain by amplification and parcial sequencing of the 16S ribosomal genes. This strain produced 0.6042 mg of betacarotene/ml of culture with 25% NaCl and 0.5% yeast extract.